Latent image - Ammer, Manuela 1977-; Ganchrow, Raviv 1972-; Lauwaert, Maaike 1978- (Roma Publications, 2016)
According to the essay by Manuela Ammer, the drawing practice of Michaela Frühwirth "responds to sites where the balance of matter and energy is negotiated, where physical force has acted on or is acting on its surroundings." It can be thought of as a negotiation of matter and energy, through works in which tons of rock detritus is transformed into a delicate web of abstract lines, or where the structure of a hydroelectric dam is detailed in countless graphite strokes. Five of Frühwirth's seemingly monolithic drawings are reproduced in this artists' book on fold-out pages and through installation views
Keywords: Frühwirth, Michaela -- 1972-; Zeichnung; Installation -- Kunst; Frühwirth, Michaela; Drawing, Netherlandish / 21st century; Installations (Art) / 21st century; Bildband